EFEK PEMBERITAAN KEKERASAN DI MEDIA SOSIAL TERHADAP CITRA NEGATIF KOTA MAKASSAR - Mukti, Imam; Oruh, Shermina; Agustang, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to identify and analyze various reports of violence that occurred in the city of Makassar through social media and the effect of reporting on violence on the formation of a negative image of the city of Makassar. This study uses a qualitative descriptive method by analyzing the content of social media and describing social media phenomena that exist in the community. This research was conducted in Makassar City using data on social media. The types and sources of data used are primary data obtained directly from a collection of screenshots of social media accounts that post various incidents of violence in the city of Makassar and secondary data, namely data obtained through literature review, documents, and relevant research results. Secondary data was collected through interviews with informants. The data were analyzed using several theories. The results of the study indicate that there are two social media that often post and report incidents of violence that occurred in the city of Makassar, namely Facebook and Instagram. Reporting through social media about the violence that occurred had a bad influence on the image formation of the city of Makassar.